Novice drivers' individual trajectories of driver behavior over the first three years of driving. (September 2015) - Roman, Gabriela D.; Poulter, Damian; Barker, Edward; McKenna, Frank P.; Rowe, Richard
Highlights: Identifying driver behavior changes in new drivers can help reduce road crash risk. Violations, errors and slips increased linearly over the first 3 years of driving. Two to three classes of aberrant driver behavior trajectories were identified. Classes of aberrant driver behavior were mainly defined by initial levels. Men and young drivers were likely following a trajectory of high aberrant behavior. Abstract: Identifying the changes in driving behavior that underlie the decrease in crash risk over the first few months of driving is key to efforts to reduce injury and fatality risk in novice drivers. This study represented a secondary data analysis of 1148 drivers who participated in the UK Cohort II study. The Driver Behavior Questionnaire was completed at 6 months and 1, 2 and 3 years after licensure. Linear latent growth models indicated significant increases across development in all four dimensions of aberrant driving behavior under scrutiny: aggressive violations, ordinary violations, errors and slips. Unconditional and conditional latent growth class analyses showed that the observed heterogeneity in individual trajectories was explained by the presence of multiple homogeneous groups of drivers, each exhibiting specific trajectories of aberrant driver behavior. Initial levels of aberrant driver behavior were important in identifying sub-groups of drivers. All classes showed positive slopes; there was no evidence of a group of drivers whose aberrant behavior decreased over time that might explain the decrease in crash involvement observed over this period. Male gender and younger age predicted membership of trajectories with higher levels of aberrant behavior. These findings highlight the importance of early intervention for improving road safety. We discuss the implications of our findings for understanding the behavioral underpinnings of the decrease in crash involvement observed in the early months of driving.